Appraisal of anti‐Parkinson activity of rhinacanthin‐C in haloperidol‐induced parkinsonism in mice: A mechanistic approach. Issue 4 (12th March 2021) - Saleem, Uzma; Gull, Zujajah; Saleem, Ammara; Shah, Muhammad Ajmal; Akhtar, Muhammad Furqan; Anwar, Fareeha; Ahmad, Bashir; Panichayupakaranant, Pharkphoom
Abstract: This study aimed to appraise the anti‐Parkinson's potential of rhinacanthin‐C (RC). RC (5, 10, and 20 mg/kg) was orally administered for 25 days in albino mice to treat haloperidol‐induced parkinsonism (1 mg/kg). RC significantly ( p < .05) improved the motor symptoms in block, bar, rotarod, and balance beam walking tests in treated mice. RC reduced the cataleptic effect dose‐dependently. The RC therapy notably ( p < .001) enhanced reduced glutathione, catalase, and superoxide dismutase levels while decreased malondialdehyde and nitrite levels in the tissue homogenates of the treated mice. The RC therapy significantly ( p < .01–.001) restored the dopamine, norepinephrine, and serotonin levels in the brain tissue of treated mice as co‐evidenced from brain histology. RC did not adversely affect complete blood count, and liver and kidney function tests. Taken together, these results have shown that RC is effective in treating motor and non‐motor symptoms of Parkinson's disease. Practical applications: Rhinacanthus nasutus is a medicinally rich plant that has folklore use in several ailments. The plant possessed multiple pharmacological activities due to the presence of naphthoquinones. The major compound of this plant rhinacanthin‐C was used in the present study to evaluate it's anti‐Parkinson's activity. The results provide scientific evidence of the anti‐Parkinson's potential of rhinacanthin‐C that support the use of R. nasutus leaves in the prevention and treatment of Parkinson's disorder. Abstract : Rhinacanthin‐C (RC) therapy substantially improved the motor symptoms and reduced the cataleptic effect dose dependently. It notably enhanced the GSH, CAT and SOD while reduced MDA and nitrite levels in brain, heart, kidney and liver homogenates of treated mice. The RC therapy significantly restored the dopamine, norepinephrine and serotonin level in brain tissue of treated mice.